Work Organisation Supported by an Expert System in Agriculture - Felföldi, János (Acta Agraria Debreceniensis, 2001)
Expert systems are softwares that incorporate the experience of an expert and support decision makers by leading them through the thinking processes of an expert in the form of „if…then” rules. To use an expert system we have to work with knowledge expressed in a pre-determined form. To do so, we used a shell that can be purchased, and we acquired knowledge about the topic from experts through interviews and personal monitoring. Attributes that are non-measurable, such as many of the factors determining work-place organisation and revealing knowledge related to it, can be formed into words by using expert systems. The goal of the study was to present a suggested form of expert system model to help judge the level of work-place organisation.